Applying strength and conditioning practices to female athletes - Read, P. J.; Montalvo, A.; Blagrove, R.; Bürden, R.; Myer, G.; Lloyd, R. S. (Routledge handbook of strength and conditioning: Sport-specific programming for high performance, 2018)
In the past, some women may not have engaged in activities such as resistance training due to misconceptions and myths centred around unwanted changes in body composition and avoidance of activities that involve high intensity or external loadings (Ebben and Jenson, 1998). A cumulative body of evidence is now available to indicate that females who participate in well-designed athletic development programmes are capable of tolerating and adapting to the stresses imposed and often experience a range of health benefits (NSCA, 1989; Kraemer et al., 2001). Improvements in strength (Kraemer et al., 2001 Myer et al., 2005), sprint speed (Myer et al., 2005), jump performance (Myer et al., 2005) and sport specific measures have been shown following training programmes that include resistance training, plyometrics and dynamic balance exercises. In addition, beneficial changes to landing mechanics and known injury risk factors are possible (Myer et al., 2005), with knee injury incidence in female athletes 3.6 times lower in trained versus un-trained participants (Hewett et al., 1999). As well as the positive effects on performance outcomes, numerous health benefits have been demonstrated following resistance training. These include enhanced bone modelling, stronger connective tissues, heightened joint stability and increases in lean body mass with concomitant reductions in fat mass. While the cumulative body of evidence suggests employing athletic development programmes with female athletes is beneficial, practitioners should be cognizant of specific sex-related differences in physical characteristics, body composition, biomechanics and training responsiveness. A deeper understanding of these factors will ensure that best practice is implemented and performance is enhanced when designing and evaluating training interventions. The aim of this chapter is to discuss key differences in strength and power development, physiological function and biomechanics in order to provide a clear practical application of how to effectively design, implement and monitor strength and conditioning provision for females.